MARKETING STRATEGY THROUGH COVID-19 PREVENTION MESSAGES IN GOJEK ADVERTISING “J3K” - Nur Hanifah, Debby; Suarli, Dimas; Cahya Indrawan, Yuvelia (QAULAN: Journal of Islamic Communication, 2021)
Advertising is a fundamental part of one of the functions of marketing strategy with the aim of not only informing the public but also aimed at influencing someone about the image of a product. The Covid-19 prevention content that is being discussed is an opportunity for the Gojek company to do marketing. Through YouTube media, the Gojek company aired the ad "J3K" Take care of health, maintain cleanliness and maintain security as an effort to prevent the spread of Covid-19. This study will reveal marketing strategies through the message of preventing Covid-19 in the Gojek "J3K" advertisement. This research uses qualitative research methods through analytical descriptive exposure. The implicit marketing strategy in the Gojek "J3K" advertisement is analyzed using semiotics from Ferdinand De Saussure. In the analysis, produced a sign (signifier), a marker (signified) and a sign (sign). The signifier in the Gojek "J3K" advertisement is recorded visually and audio in the advertisement so that there are similarities in the meaning of the sign. After knowing the signifier, an agreement will be obtained on the concept of sign meaning in the form of a signified. Keywords: Advertising, Marketing Strategy, Covid-19, Semiotics